Preliminary Results of High-Precision Computed Diffusion Weighted Imaging for the Diagnosis of Hepatocellular Carcinoma at 3 Tesla. Issue 3 (May 2018) - Akagi, Motonori; Nakamura, Yuko; Higaki, Toru; Matsubara, Yoshiko; Terada, Hiroaki; Honda, Yukiko; Tatsugami, Fuminari; Baba, Yasutaka; Iida, Makoto; Awai, Kazuo
Abstract : Objective: To compare the utility of high-precision computed diffusion-weighted imaging (hc-DWI) and conventional computed DWI (cc-DWI) for the diagnosis of hepatocellular carcinoma (HCC) at 3 T. Methods: We subjected 75 HCC patients to DWI ( b -value 150 and 600 s/mm 2 ). To generate hc-DWI we applied non-rigid image registration to avoid the mis-registration of images obtained with different b -values. We defined c-DWI with a b -value of 1500 s/mm 2 using DWI with b -value 150 and 600 s/mm 2 as cc-DWI, and c-DWI with b -value 1500 s/mm 2 using registered DWI with b -value 150 and 600 s/mm 2 as hc-DWI. A radiologist recorded the contrast ratio (CR) between HCC and the surrounding hepatic parenchyma. Results: The CR for HCC was significantly higher on hc- than cc-DWIs (median 2.0 vs. 1.8, P < 0.01). Conclusion: The CR of HCC can be improved with image registration, indicating that hc-DWI is more useful than cc-DWI for the diagnosis of HCC.